Oral Manifestations of Systemic Lupus Erythematous and Its Comprehensive Management: Two Case Reports - Rita Wardhani; Irna Sufiawati (Majalah Kedokteran Bandung, 2018)
Systemic lupus erythematous (SLE) is an autoimmune collagen-vascular disease involving mucocutaneous and musculoskeletal systems as well as blood vessels that is characterized by diverse clinical manifestations, making it necessary to use a comprehensive multidisciplinary approach. Oral manifestations of SLE include oral ulcer, discoid lesions, oral lichen planus-like-lesion, oral candidiasis, and xerostomia. This study reports two cases of 19-year-old and 41-year-old female patients visiting the Oral Medicine Department Dr. Hasan Sadikin General Hospital in October 2016. These patients were referred by the Internal Medicine Department with SLE diagnosis, involving hematological, musculoskeletal and mucocutaneous systems. Extraoral examination revealed moon face in the first patient and malar rash and lips exfoliations in the second  patient. Intraoral examination revealed oral ulcers on buccal and labial mucosa as well palate in both patients. Both patients were given methyl prednisolone, calcium, and folic acid by the Internal Medicine Department. Oral ulcers were treated with prednisone mouthwash, nystatin oral suspension, and vitamin B12. The oral ulcer on palate was considered very difficult to resolve so that topical corticosteroid was required. Prednisone mouthwash was chosen as drug of choice due to its efficacy on oral mucosa and its ability to minimize the systemic adverse effects which were resolved in 6 week after starting treatment. Comprehensive multidisciplinary approach associated with oral manifestation of SLE has significant effects in decreasing disease severity and improving the quality of life in patients with SLE.Key words: Oral ulcers, prednisone mouthwash, systemic lupus erythematosus Manifestasi Oral Lupus Eritematosus Sistemik dan Manajemen Komprehensifnya: Dua Laporan KasusSistemik lupus eritematosus (SLE) adalah penyakit kolagen-vaskular autoimun, yang melibatkan sistem mukokutan, muskuloskeletal, dan pembuluh darah yang ditandai dengan manifestasi klinis yang bervariasi, sehingga diperlukan pendekatan multidisiplin yang komprehensif. Manifestasi oral SLE meliputi ulkus mulut lesi diskoid, lichen planus-like lesion, kandidiasis oral, dan serostomia. Pasien wanita berusia 19 tahun dan 41 tahun yang dirujuk dari departemen Penyakit Dalam pada Oktober 2016 dengan diagnosis SLE yang melibatkan hematologis, muskuloskeletal, dan mukokutan. Pemeriksaan ekstraoral menunjukkan moon face pada pasien pertama, dan malar rash serta pengelupasan bibir pada pasien kedua. Pemeriksaan intra oral mengungkapkan ulkus oral, mukosa labial, dan palatum pada kedua pasien. Kedua pasien diberikan metil prednisolone, kalsium, dan asam folat dari departemen Penyakit Dalam. Ulkus oral diobati dengan obat kumur prednison, suspensi oral Nistatin, dan vitamin B12 yang diberikan dalam 6 minggu pengobatan. Ulkus oral adalah salah satu manifestasi oral yang umum pada pasien SLE. Ulkus oral pada palatum dianggap sangat sulit diatasi sehingga dibutuhkan kortikosteroid topikal. Prednisone mouth wash dipilih sebagai obat pilihan sebagai anti-inflamasi pada mukosa oral dan meminimalkan efek samping sistemik. Pendekatan multidisiplin komprehensif yang terkait dengan manifestasi oral SLE memiliki efek signifikan dalam menurunkan tingkat keparahan penyakit dan meningkatkan kualitas hidup pada pasien SLE.Kata kunci: Lupus eritematosus sistemik, ulser oral, obat kumur prednison